2020
DOI: 10.1002/jmrs.405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiation doses between diagnostic full‐field digital mammography (FFDM) and digital breast tomosynthesis (DBT): a clinical study

Abstract: Introduction There are increasing concerns about radiation exposure among women who undergo full‐field digital mammography (FFDM) and digital breast tomosynthesis (DBT). The main aim of this study was to compare the entrance surface dose (ESD) and average glandular dose (AGD) from FFDM and DBT for different breast thicknesses. Methods The ESD and AGD for FFDM in craniocaudal, mediolateral oblique and DBT in craniocaudal projection were recorded from a GE Senographe Essential FFDM unit. The accuracy of the ESD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We found that the AGD between two-view-FFDM and single view DBT, CC-DBT and MLO-DBT, MLO-FFDM+CC-DBT and CC-FFDM + MLO-DBT were similar (p>0.05), indicating that any collection method within these three combinations can be used interchangeably. Moreover, the AGD of single view DBT was equal to or lower than that of two-view FFDM, which was consistent with the study from Asbeutah et al, 10 but the lesion display efficiency of single view DBT was lower. On the other hand, MLO-FFDM+CC-DBT and CC-FFDM+MLO-DBT could provide rich image information for dense breasts, and the relative dose rates of the two combinations did not exceed 1.52 times of two-view FFDM; moreover, their radiation dose can be further reduced by reducing the compression thickness.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the AGD between two-view-FFDM and single view DBT, CC-DBT and MLO-DBT, MLO-FFDM+CC-DBT and CC-FFDM + MLO-DBT were similar (p>0.05), indicating that any collection method within these three combinations can be used interchangeably. Moreover, the AGD of single view DBT was equal to or lower than that of two-view FFDM, which was consistent with the study from Asbeutah et al, 10 but the lesion display efficiency of single view DBT was lower. On the other hand, MLO-FFDM+CC-DBT and CC-FFDM+MLO-DBT could provide rich image information for dense breasts, and the relative dose rates of the two combinations did not exceed 1.52 times of two-view FFDM; moreover, their radiation dose can be further reduced by reducing the compression thickness.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of the anti-scatter grid is more pronounced when used against patients with relatively thicker breast because thicker breast contributes high scatter radiation than thinner breast. A clinical study carried out in Kuwait by using the same mammography vendor (GE Senographe Essential) demonstrated a similar finding where a single-view DBT (1.8 to 4.0 mGy) yielded lower AGD than the two-view FFDM technique (3.3 to 6.0 mGy) [ 8 ]. Furthermore, 84% of the patient population in the Kuwait study comprises of 4–7 cm thickness, which is considered thicker breast owing to the lower dose of DBT than FFDM.…”
Section: Discussionmentioning
confidence: 81%
“…Gennaro et al (2018) showed that the average increase in the dose of DBT compared to FFDM was 38% [ 7 ]. While the study by Asbeutah et al showed that the AGD for a single-view DBT 45–50% was lower than the two-view FFDM technique [ 8 ]. However, Gilbert et al concluded that adding DBT to FFDM doubles the radiation dose a woman would receive in routine breast screening [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previously published studies investigated the radiation risk from diagnostic two-view FFDM and compared it with that from single-view DBT in a phantom study [ 7 ] and a human study. [ 8 ] However, our primary aim of this study was to evaluate whether the radiation dose depends on the data derived from a mammography unit picture archiving and communication system (PACS) data.…”
Section: Introductionmentioning
confidence: 99%